Ventriculoperitoneal Shunt Infection Caused by Enterococcus gallinarum in a Pediatric Patient: A Case Report - Clark, Kacie; Maka, Deborah (Journal of Pediatric Intensive Care, 2019)
Enterococcus gallinarum is a common colonizer of the gastrointestinal tract that expresses intrinsic vancomycin resistance. This case report describes an E. gallinarum ventriculoperitoneal (VP) shunt infection in a pediatric patient. A 4-year-old female patient presented with cerebrospinal fluid (CSF) cultures from a VP shunt significant for E. gallinarum. The patient received ampicillin and synergistic gentamicin. She completed a total of 16 days of therapy following 2 weeks of negative CSF and blood cultures with full clinical cure of infection. The patient was successfully treated following a 2-week course of antibiotics. Awareness of Enterococcus species with intrinsic vancomycin resistance should be increased.
Keywords: Enterococcus; ventriculoperitoneal shunt; meningitis